PENGARUH PEMASARAN DIRECT SELLING TERHADAP MINAT BELI KONSUMEN SEGMEN GENERAL TRADE DI PT XYZ - Salsabiila, Defira; Pardian, Pandi (Universitas Galuh, 2023)
Direct selling involves the process of communicating products and the ability of the sales force to build trust, fulfil special requests, anticipate customer desires, make offers so buyers have an interest in buying the products offered. Direct selling has a big role in consumer buying interest, where the consumer's perception of the sales force includes its ability to influence consumer intentions to make purchases or what is called buying interest. This study aims to determine direct selling and consumer buying interest in the general trade segment at PT XYZ and to determine the effect of direct selling marketing on consumer buying interest in the general trade segment at PT XYZ. This research was conducted using a quantitative approach and survey research methods using a questionnaire. Data analysis used is descriptive analysis, simple linear regression, and t test. The results showed that direct selling marketing in the general trade segment at PT XYZ has a good category for communication skills, product knowledge, creativity, and empathy in making direct offers and sales, buying interest consumers in the general trade segment at PT XYZ has a good category for attention. , interests, desires, and actions of consumers in the general trade segment towards direct offers and sales. The results showed positive influence towards direct selling on consumer buying interest in the general trade segment at PT XYZ. This is because consumer buying interest in the general trade segment at PT XYZ is influenced by the ability of the sales force and interpersonal relationships between buyers and sellers in offering and making direct sales.